2017
DOI: 10.1186/s12913-017-2537-0
|View full text |Cite
|
Sign up to set email alerts
|

Role enactment of facilitation in primary care – a qualitative study

Abstract: BackgroundFacilitation is a widely used implementation method in quality improvement. Reviews reveal a variety of understandings of facilitation and facilitator roles. Research suggests that facilitation interventions should be flexible and tailored to the needs and circumstances of the receiving organisations. The complexity of the facilitation field and diversity of potential facilitator roles fosters a need to investigate in detail how facilitation is enacted. Hence, the purpose of this study was to explore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(40 citation statements)
references
References 46 publications
0
40
0
Order By: Relevance
“…Given the complexity of implementation facilitation, it is not surprising scholars suggest that facilitators need a diverse range of knowledge and skills that they can apply depending on the purpose and context of their efforts [ 13 , 28 30 ]. Lack of these skills may compromise fidelity to the planned facilitation intervention and negatively influence outcomes [ 31 34 ]. Thus, studies or clinical initiatives applying facilitation as an implementation strategy need to ensure that facilitators have the necessary skills or provide training for developing those skills [ 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…Given the complexity of implementation facilitation, it is not surprising scholars suggest that facilitators need a diverse range of knowledge and skills that they can apply depending on the purpose and context of their efforts [ 13 , 28 30 ]. Lack of these skills may compromise fidelity to the planned facilitation intervention and negatively influence outcomes [ 31 34 ]. Thus, studies or clinical initiatives applying facilitation as an implementation strategy need to ensure that facilitators have the necessary skills or provide training for developing those skills [ 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…doi: 10.22454/FamMed.2019.774561 are limited. 2,3,6,7,11,19,20 Much research focuses on external practice facilitators who, coming into an organization from the outside, may need different skills to work with an unfamiliar group. 1,21 The goal of this project was to explore attributes of internal staff identified by family medicine residency directors as "people in the office or clinic who make things easier."…”
Section: Discussionmentioning
confidence: 99%
“…The intervention has been described in more detail elsewhere [ 13 ]. As researchers, our role was to study the intervention and we were not involved in either the design or the implementation of the intervention.…”
Section: Methodsmentioning
confidence: 99%
“…The intervention relied on general practitioners (GPs) as facilitators. In two previous studies, we explored how facilitation was enacted in this intervention and the effectiveness of the intervention [ 12 , 13 ]. First, based on observations and interviews with facilitators we found that facilitation was enacted through four major roles: the teacher (knowledge dissemination), the super user (hands-on knowledge dissemination on the practice’s computer system), the peer (facilitators conveying their experiences and information about their own practice organisation), and the process manager (selection of topics, tasks, and status reporting at subsequent visits).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation